Mothers' and fathers' perceptions of marital relationships and coparenting twins during school transition. Issue 1 (2nd January 2022) - Latham, Rachel M.; Mark, Katharine M.; Oliver, Bonamy R.
ABSTRACT: Coparenting and the marital relationship are closely related yet distinct family subsystems hypothesized to influence one another. Little is known about these processes with consideration of more than one child in the family, which may have important implications. Here, we specifically focus on families with young twins, enabling us to account for sibling age-difference confounds, as well as due to the greater parenting demands and higher divorce rates in twin families. Using cross-lagged models for both mothers and fathers, we examined bidirectional associations between coparenting and the marital relationship during children's transition to formal schooling. Parents of twins from 107 'intact' families reported perceptions of coparenting and the marital relationship via telephone interview at Time 1 ( M child age  = 4years 8 months, SD child age  = 4.44 months) and questionnaire at Time 2 ( M child age  = 6 years, SD child age  = 6.12 months). Accounting for within-time associations and temporal stability for both mothers and fathers, coparenting was positively associated with subsequent reports of the marital relationship; there was no evidence of reciprocal associations between the marital relationship and subsequent coparenting. As children transition to primary school, the quality of coparenting may be a driver of the quality of the marital relationship for parents of twins. Those seeking to improve the marital relationship should pay due attention to perceptions of coparenting.